Human papillomavirus (HPV) vaccination for the prevention of HPV 16/18 induced cervical cancer and its precursors - Damm, Oliver (German Medical Science GMS Publishing House, 2009)
INTRODUCTION: Essential precondition for the development of cervical cancer is a persistent human papillomavirus (HPV) infection. The majority - approximately 70% - of cervical carcinomas is caused by two high-risk HPV types (16 and 18). Recently, two vaccines have been approved to the German market with the potential to induce protection against HPV 16 and HPV 18 among additional low-risk virus types. OBJECTIVES: To analyse whether HPV vaccination is effective with regard to the reduction of cervical cancer and precursors of cervical carcinoma (CIN), respectively? Does HPV vaccination represent a cost-effective alternative or supplement to present screening practice? Are there any differences concerning cost-effectiveness between the two available vaccines? Should HPV vaccination be recommended from a health economic point of view? If so, which recommendations can be conveyed with respect to a (re)organization of the German vaccination strategy? Which ethical, social and legal implications have to be considered? METHODS: Based on a systematic literature review, randomized controlled trials (RCT) looking at the effectiveness of HPV vaccination for the prevention of cervical carcinoma and its precursors - cervical intraepithelial neoplasia - have been identified. In addition, health economic models were identified to address the health economic research questions. Quality assessment of medical and economic literature was assured by application of general assessment standards for the systematic and critical appraisal of scientific studies. RESULTS: Vaccine efficacy in prevention of CIN 2 or higher lesions in HPV 16 or HPV 18 negative women, who received all vaccination doses, ranges between 98% and 100%. Side effects of the vaccination are mainly associated with injection site reactions (redness, turgor, pain). No significant differences concerning serious complications between the vaccination- and the placebo-groups were reported. Results of base case scenarios in the identified health economic modeling analyses range from approximately 3,000 Euro to 40,000 Euro per additional QALY (QALY = Quality-adjusted life year) and approximately 9,000 Euro to 65,000 Euro per additional life year (LYG), respectively. DISCUSSION: The included studies show that both available HPV vaccines are effective in preventing HPV 16 and HPV 18 infections and probable resulting premalignant lesions of the cervix. However, the duration of protection is currently unclear. With regard to side effects, the vaccination can be considered as secure. Nevertheless, the number of cases within the clinical studies is not sufficient to determine the occurrence of rarely occurring (severe) adverse events in a reliable way. A reduction in the incidence and induced mortality through cervical cancer in Germany is not only depending on the vaccine’s clinical efficacy. Effects of the new technology on the overall participation rate in screening programs and the resulting vaccination rate and immunization status are also important factors. The results of identified health economic models vary substantially due to the heterogeneity of methodological approaches as well as chosen input parameters. However, almost all model-based analyses reached the conclusion that the implementation of a vaccination with lifelong protection can be considered as cost-effective, if the present screening practice continues. A comparison of the two vaccines shows, that the cost effectiveness ratios are more favorable with the quadrivalent vaccine than with the bivalent alternative when considering QALY as primary outcome parameter. The reason for this finding might be that in the case of the quadrivalent vaccine the prevention of genital warts can also be incorporated into the analysis. Variations of the duration of protection as well as the discounting rate were identified as the primary influencing factors of cost-effectiveness results. CONCLUSION: Implementation of HPV vaccination might lead to a reduction of cervical cancer in immunized women. However, uptake of immunization should be accompanied by further studies in order to assess long-term effectiveness and safety aiming at an optimization of possible implementation processes. High numbers of participants are of particular importance regarding immunization. This has to be backed up by programs to optimize early detection – as this affects even those women who already underwent immunization. Since cost-effectiveness evidence might be significantly affected by the unclear duration of protective benefits, a final verdict on the vaccination’s cost-effectiveness in the German setting is not possible. Hence, risk-sharing-agreements between third-party payers and manufacturers would pose an option to balance the consequences of uncertainty towards the duration of protection on cost-effectiveness.